A study of disorder shell effects on the mechanical properties of SiC nanowires - Zheng, Bin (Strojniški vestnik, 2015)
The mechanical properties of SiC nanowires were investigated using molecular dynamics simulation method. The results show that the disorder shell layer reduced the elastic modulus of SiC nanowires. This reduction mainly depends on the thickness and the atomic type of the disorder shell. Thicker C and Si disorder layers can strengthen and weaken the nanowires, respectively. Also, the core-shell wires have size- dependent strength, which can be understood by examining the variation of Young's modulus and the volume fraction of the isolated core and isolated shell. Furthermore, the disorder coating was found to facilitate the brittle-ductile transition in the SiC core. The simulation results are expected to help the design and manufacturing of complex nanoscale architectures with desired mechanical properties.
Keywords: duktilnost; mehanske lastnosti; modul elastičnosti; nanožica vrste jedro-lupina; nanožice; simulacija molekularne dinamike; vpliv velikosti